Phylogeography of msp4 genotypes of anaplasma marginale in beef cattle from the Brazilian pantanal - Ramos, Inalda Angélica de Souza [UNESP]; Herrera, Heitor Miraglia; Mendes, Natália Serra [UNESP]; Fernandes, Simone de Jesus [UNESP]; Campos, João Bosco Vilela; Alves, João Vitor Almeida; Macedo, Gabriel Carvalho de; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (FapUNIFESP (SciELO), 2019)
The msp4 gene of A. marginale is unicodon, stable and mostly homogeneous, being considered as a useful marker for phylogeographic characterization of this bacterium. The objective of this work was to analyze the phylogeography of A. marginale based on the msp4 gene in beef cattle from the Brazilian Pantanal, compared to those found in other regions worldwide. The blood samples investigated were collected from 400 animals (200 cows and 200 calves) reared in five extensive breeding farms in this region. The results indicated that of the evaluated samples, 56.75% (227/400) were positive for A. marginale based on the msp1β gene by quantitatitve PCR (qPCR), while 8.37% (19/227) were positive for the msp4 gene in the conventional PCR. In the Network distance analysis, 14 sequences from the Brazilian Pantanal were grouped into a single group with those from Thailand, India, Spain, Colombia, Parana (Brazil), Mexico, Portugal, Argentina, China, Venezuela, Australia, Italy and Minas Gerais (Brazil). Among 68 sequences from Brazil and the world, 15 genotypes were present while genotype number one (#1) was the most distributed worldwide. Both Splitstree and network analyses showed that the A. marginale msp4 sequences detected in beef cattle from the Brazilian Pantanal showed low polymorphism, with the formation of one genogroup phylogenetically related to those found in ruminants from South and Central America, Europe, and Asia.
Filogeografia de genótipos msp4 de Anaplasma marginale em gado de corte no Pantanal Brasileiro
Keywords: Bovine anaplasmosis; Geographic distribution; Msp4; Nelores